Total Run-of-River type Hydropower Potential of Nepal - Jha, Raghunath (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
The total hydropower potential of Nepal was assessed as 83,500 MW in 1966 by Dr. Hari Man Shrestha dur-ing his PhD research work in former USSR. Since then, no further study has been done in this feld. The hydropower potential estimate has been used by Nepal Electricity Authority (NEA), Water and Energy Commission Secretariat (WECS) and Department of Electricity Development (DOED) for power development, licensing and policy making. However, keeping in view recent advancements in computer technology that offer many benefits to the field of water resources and the importance of power estimation in Nepal, Dr. Shrestha’s estimate needs further review and updat-ing. The present study has mainly used the hydro-meteorological data of Department of Hydrology and Meteorology (DHM) for hydrological analysis of all the rivers in Nepal including the three big rivers, viz., Saptakoshi, Narayani and Karnali, and other medium and small rivers. Incorporating GIS and the Hydropower Model that has specifcally been developed by the author, the power potential and annual energy estimate on an run-of-the-river (ROR) basis of the entire country has been worked out. The result shows that the power potential and annual energy estimates of Na-rayani, Saptakoshi and Karnali River basins at Q40% (fow exceedence) and 80% efficiency are 17800, 17008, 15661 MW and 113373, 108817, 102324 GWh, respectively. The Mahakali River would yield only 2262 MW of hydropower and 14981 GWh of energy annually. The other water sources in Nepal would have a total power potential of 1105 MW and a combined annual energy of 7043 GWh. Thus, the total hydropower potential and corresponding annual energy capacity of Nepal on a ROR basis at Q40%, and 80% efficiency is 53,836 MW and 346538 GWh, respectively. Key words: Hydropower potential; Run-of-River (ROR); GIS; Hydropower Model; Nepal DOI: 10.3126/hn.v7i0.4226 Hydro Nepal Journal of Water, Energy and Environment Vol 7, July, 2010 Page: 8-13 Uploaded date: 31 January, 2011